2010
DOI: 10.1002/ejlt.200900070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monoacylglycerols on growth inhibition of micromycetes in vitro and on bread

Abstract: The antifungal activity of monoacylglycerols with 8, 10 and 12 carbon chains (1-monocaprylin, 1-monocaprin and 1-monolaurin) against filamentous fungi isolated from contaminated bread (Penicillium piceum, Penicillium chrysogenum, Penicillium sp. and Monascus ruber) as well as against the selected microorganisms (Aspergillus niger, Penicillium roqueforti, Penicillium jensenii, Alternaria sp. and Phoma sp.) was investigated. All the tested monoacylglycerols showed antifungal efficacy at concentrations equal to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The susceptibility of yeast and fungi is also species specific. While we found a MIC of 4 mM for Z. bailii, previous studies have documented MIC values ranging from 0.15 to 10 mM for a wide range of yeast and fungi (5,7). Interestingly, the MIC of bacteria was similar to the concentration for which no viable cells were detected, and growth inhibition was thus directly linked to loss of viability (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The susceptibility of yeast and fungi is also species specific. While we found a MIC of 4 mM for Z. bailii, previous studies have documented MIC values ranging from 0.15 to 10 mM for a wide range of yeast and fungi (5,7). Interestingly, the MIC of bacteria was similar to the concentration for which no viable cells were detected, and growth inhibition was thus directly linked to loss of viability (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…and Aspergillus spp. (7), and herpes simplex virus (21). The mode of action for monocaprylate has not yet been investigated, and we hypothesize that it is similar to that of other monoglycerides.…”
mentioning
confidence: 92%
“…The high tolerance of this fungus to MAG activity was also reported by Růžička (2003). Buňková (2010) found that the growth of some penicillia including P. roqueforti was strongly inhibited by MAG C10:0 and MAG C12:0 while a weak inhibitory action on A. niger was recorded. In our study, the behaviour of these strains with respect to MAGs showed similar features.…”
Section: Antifungal Activity Of Mags In Vitrosupporting
confidence: 72%
“…MAG have attracted their interest due to relatively simple structure, availability, chemical stability and first of all due to their biocompatibility, biodegradability and absence of irritable effect on humans. MAG are generally recognised as safe (GRAS) and can be applied with a great confidence not only in foods [3,4] and feeds [5] but also in pharmaceutical industry, medicine [6] and cosmetics. Moreover, they can be used in production of antimycotic materials getting into touch with skin, products preventing fermentation, etc.…”
Section: Introductionmentioning
confidence: 99%